Quantum phenomena in transport measurements of topological insulator nanostructures (Review Article) - Fang, L.; Kwok, W.-K. (Физика низких температур, 2014)
We review the recent experimental advances on quantum phenomena in transport measurements of topological insulators with emphasis on quantum oscillation, weak antilocalization and Aharonov–Bohm effect and Altshuler–Aronov–Spivak effect. Following a brief introduction on the topic, we discuss the identification of the
topological surface state based on quantum phenomena. Research prospect of topological insulators is described at the end of this article.